Metazoan tRNA introns generate stable circular RNAs in vivo. - Lu, Z.; Filonov, G.S.; Noto, J.J.; Schmidt, C.A.; Hatkevich, T.L.; Wen, Y.; Jaffrey, S.R.; Matera, A.G. (RNA (New York, N.Y.), 2015)
We report the discovery of a class of abundant circular noncoding RNAs that are produced during metazoan tRNA splicing. These transcripts, termed tRNA intronic circular (tric)RNAs, are conserved features of animal transcriptomes. Biogenesis of tricRNAs requires anciently conserved tRNA sequence motifs and processing enzymes, and their expression is regulated in an age-dependent and tissue-specific manner. Furthermore, we exploited this biogenesis pathway to develop an in vivo expression system for generating "designer" circular RNAs in human cells. Reporter constructs expressing RNA aptamers such as Spinach and Broccoli can be used to follow the transcription and subcellular localization of tricRNAs in living cells. Owing to the superior stability of circular vs. linear RNA isoforms, this expression system has a wide range of potential applications, from basic research to pharmaceutical science.